Character Education Values in Adolescents’ Upstander Behavior Against Cyberbullying on TikTok - Husna, Sofiatul; Maemonah (FOUNDASIA, 2025)
This study aims to identify character education values that shape adolescents’ upstander behavior toward cyberbullying on TikTok, with a particular focus on adolescents in rural communities. Cyberbullying, especially on social media platforms such as TikTok, has become a serious issue with significant impacts on adolescents’ mental and social well-being. Although many adolescents recognize cyberbullying as inappropriate behavior, a gap frequently exists between moral understanding and actual behavior. This study employed a descriptive qualitative approach through in-depth interviews with 15 adolescents aged 12 to 18 who were active TikTok users and had witnessed or been involved in cyberbullying situations. The findings indicate that although most adolescents understand cyberbullying as morally wrong (moral knowing), not all of them act as upstanders (moral action) due to strong social influences, such as fear of social exclusion or uncertainty about how to respond appropriately. Furthermore, empathy (moral feeling) arising from concern for victims does not always translate into action. Limited digital literacy and inadequate infrastructure in rural communities further exacerbate adolescents’ responses to cyberbullying. This study concludes that effective character education should integrate Lickona’s moral dimensions with digital literacy to foster adolescents who are more responsive to cyberbullying. These findings are significant for the development of educational policies that support adolescents’ active roles in addressing cyberbullying in the digital era.